Do UOC Students Fit in the Net Generation Profile? An Approach to their Habits in ICT Use - Romero, Marc; Guitert, Montse; Sangrà, Albert; Bullen, Mark (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Some authors have stated that university students born after 1982 have been profoundly influenced by digital technologies, showing different characteristics when compared to previous generations. However, it is worth asking if that is a current observable phenomenon. Are those students born after the 80s really more familiar with ICT tools than those born in previous generations? Do they show different study habits and learning paths? Different research lines (Kennedy, et al., 2010; Bennett, Maton, & Kervin, 2008; Gros, García, & Escofet, 2012) highlight that scientific data is rarely used when discussing this generation’s characteristics; however, none of them have proved in statistical terms that college students do not fit in the Net Generation characteristics and that their habits of ICT use in social and professional activities do not differ from older generations. The international research project, Digital Learners in Higher Education, seeks to develop a sophisticated and evidence-based understanding of university learners in different institutional contexts and the perception of cultures in their use of technology in a social and educational context. Data has been collected from four institutions in Canada and Spain: the British Columbia Institute of Technology, the University of Regina, the Open University of Catalonia (UOC), and the University Rovira i Virgili. In order to develop this project, we used a multi-case study embedded design (Yin, 2009). The UOC’s case is deeply analysed in this paper to affirm that the Net Generation is more speculative than real and that includes students’ perception about this phenomenon, and guidelines are proposed in an eLearning context.